2003
DOI: 10.1007/bf02803144
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification of arbuscular mycorrhizal fungi in roots: Perspectives and problems

Abstract: Molecular identification methods are about to revolutionize studies on ecology of arbuscular mycorrhiza. These techniques offer the unique opportunity to investigate communities of arbuscular mycorrhizal fungi (AMF) within roots. Recent technical advances are reviewed, discussing their drawbacks and advantages. An experimental approach to analyze AMF communities within roots using a molecular identification method is presented. Sample results from the analysis of trap cultures from a current project are shown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0
4

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(64 citation statements)
references
References 45 publications
(29 reference statements)
0
60
0
4
Order By: Relevance
“…The morphological identification method had obvious limitations to study AMF biodiversity, as reliable results always require the proficiency of the identifier, and the sporulation of AMF may depend on environmental conditions. Under certain circumstance or during certain seasons of the year, some AMF may not produce spores at all (Redecker et al, 2003). By contrast, molecular identification techniques provided a powerful tool to identify AMF in any given roots or soil samples without the need for spores.…”
Section: Discussionmentioning
confidence: 99%
“…The morphological identification method had obvious limitations to study AMF biodiversity, as reliable results always require the proficiency of the identifier, and the sporulation of AMF may depend on environmental conditions. Under certain circumstance or during certain seasons of the year, some AMF may not produce spores at all (Redecker et al, 2003). By contrast, molecular identification techniques provided a powerful tool to identify AMF in any given roots or soil samples without the need for spores.…”
Section: Discussionmentioning
confidence: 99%
“…Although the three well-established families of the Glomeromycota, i.e., Glomaceae, Acaulosporaceae, and Gigasporaceae, can be amplified, some species in the two deeply branching and less commonly found families of Archaeosporaceae and Paraglomeraceae may not be detected when this primer pair is applied to environmental samples (Redecker, 2000). ARCH1311, which is specific to the two deeply branching families (Redecker, 2000), together with primers targeting other groups of AMF species, has been used to detect the largest portion of taxon diversity in the Glomeromycota (Redecker, 2000;Redecker et al, 2003;Hijri et al, 2006). DGGE analysis using the combination of those primers, however, has not been worked out yet.…”
Section: Nested Pcr and Dggementioning
confidence: 99%
“…Based on the lack of sexual reproduction in AMF, it has been suggested that applying the species concept could be difficult and that it would be more appropriate to base the description of biodiversity on genetic diversity (Sanders et al 1996). However, even for interpretation of the most recent molecular ecological studies, genetic variation within one population and among different isolates of one species can be quite high (Antoniolli et al 2000;Clapp et al 2001;Redecker et al 2003). Morphospecies are units of classical taxonomy and units of experimental manipulation when linking organismal and molecular scales.…”
Section: Species Richness and Community Diversity Across Chinamentioning
confidence: 99%